Sisa Makan di Penyelenggaraan Makanan di Rumah Sakit Islam Aminah Kota Blitar - Kris Diah Ajeng R.S; Enggar Anggraeni; Mirthasari Palupi (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
The quality of nutrition services in hospitals is an important thing to pay attention to. One indicator of hospital nutrition service standards is the patient's leftover food <20%, which is the minimum standard that has been set by the hospital. The patient's food waste is influenced by several factors, including internal factors, namely psychological conditions, physical conditions and eating habits. External factors are the taste of food, appearance of food (food color, texture and shape of food, large portions and presentation of food), while in terms of environmental factors (time of feeding, food utensils and food waiters). This descriptive study with 15 respondents aims to determine the description of food waste in the food service at Aminah Islamic Hospital in Blitar City. Perceptions about food are known by interview method, and observing the patient's leftover food for 3 days with a visual estimate of the Comstock 6 point. The results showed that most of the respondents during the day more often consumed food brought by their family from outside the hospital. This can be seen in the reports of the patient's average leftover food as follows: rice 69.80%, animal side dishes 57.20%, vegetable side dishes 74.25% and vegetables 49.80%. It is recommended that the processing method can be modified so that it can improve the taste, texture and aroma with the purpose that it is more attractive to the patient's appetite and reduces food waste. Motivating patients to maintain the intake served by the hospital is a supporting factor in the healing process.